2010
DOI: 10.1007/s11340-010-9345-3
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Shock Resistance of a Kyanite-Based (Aluminosilicate) Ceramic

Abstract: This paper presents the results of a combined experimental and theoretical study of microstructure and thermal shock resistance of an aluminosilicate ceramic. Shock-induced crack growth is studied in sintered structures produced from powders with different particle size ranges. The underlying crack/microstructure interactions and toughening mechanisms are elucidated via scanning electron microscopy (SEM). The resulting crack-tip shielding levels (due to viscoelastic crack bridging) are estimated using fracture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…This can be attributed to the decomposition of the kyanite into mullite phase and SiO 2 at 1500 • C. The synthesis of mullite occurred through the reaction between SiO 2 and alumina in the coating slurry, as described by Equations ( 5) and (6). The results of XRD indicate that after pressureless sintering at 1600 • C for 2 h, the kyanite phase in the coating was almost completely transformed into the mullite phase, which agrees with the results from other researchers [12,13].…”
Section: Microstructure and X-ray Diffractionsupporting
confidence: 89%
See 1 more Smart Citation
“…This can be attributed to the decomposition of the kyanite into mullite phase and SiO 2 at 1500 • C. The synthesis of mullite occurred through the reaction between SiO 2 and alumina in the coating slurry, as described by Equations ( 5) and (6). The results of XRD indicate that after pressureless sintering at 1600 • C for 2 h, the kyanite phase in the coating was almost completely transformed into the mullite phase, which agrees with the results from other researchers [12,13].…”
Section: Microstructure and X-ray Diffractionsupporting
confidence: 89%
“…However, it is observed that the residual flexural strength of ZTA at 300 • C and kyanite-coated ZTA at 400 • C shows a steep fall. The critical temperature, at which the strength sharply drops off after quenching, is widely recognized as a crucial indicator for evaluating thermal shock resistance [13], but at the same quenching temperature, the strength of kyanite-coated ZTA is consistently greater than that of ZTA. Combined with Figure 6, it shows that after quenching, the surface of the ZTA produces a large number of small irregular cracks, and even some of the cracks have been extended; however, on the surface of the kyanite-coated ZTA, small cracks formed after quenching, and did not expand or connect with each other.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…The early crystallization of the refractory at the temperature range between 850 ℃ and 1050 ℃ is as a result of the dopant (mineralizer)-slaked lime and the OH -group in opal, the presence of which lowers the inversion temperature of silica polymorphs [6][7][8][9]13,14]. In fact, Nayak and Bera [6] have reported that complete crystallization of RHS with 99.87% purity only takes place at about 1300 ℃.…”
Section: Phase Transitions and Thermal Expansion Studiesmentioning
confidence: 99%
“…For instance, anorthite was detected in the sintered refractory. One of the positive effects of these visco-elastic phases is that they are capable of forming shields around crack-tips, thus leading to better thermal shock resistance [8].…”
Section: Phase Transitions and Thermal Expansion Studiesmentioning
confidence: 99%
See 1 more Smart Citation